Art and Science: Three epistemic annotations for an interdisciplinary study - Calvo Díaz, Andrea (2019)
The present article analyzes from an epistemic and reflective perspective the importance of academic praxis in art and science with respect to the interdisciplinary studies enunciated by Rolando García. For this, three aspects of the study have been formulated: disciplinary assessment, methodological rigor, and humanistic and ethical dimension in the interdisciplinary exercise. In addition, it is taking into consideration the intellectual approach of Leonardo da Vinci (1452-1519) and Galileo Galilei (1564-1642) to justify the annotations to wield. In this way, it is concluded that art and science assume convergent points in the disciplinary work, without neglecting that each area maintains a different approach in the way of approaching an experiment, a problem or a process. On the other hand, despite the relationship between both disciplines (an example, the use of drawing) a different methodological rigor persists in the study approach. Finally, both disciplines assume a humanist task in the elaboration of their statements and results.